Livestock development strategies for low income countries. Proceedings of a roundtable - Wilson, R.T.; Ehui, Simeon K.; Mack, S. (Food and Agriculture Organization of the United Nations, 1995)
This volume contains an executive summary of papers and the discussions on them as well as the reports of working groups and the recommendations of the Roundtable on Livestock Development strategies for Low Income Countries. In addition to the executive summary there is a Keynote paper and two other background papers, two papers on issues, constraints and opportunities for livestock development and five papers on options for increasing livestock's contribution from the major production systems. The volume also contains reports of all the discussions and summarized reports of the working groups that were convened for subSaharan Africa and West Asia and North Africa, Asia, and Latin America and the Caribbean. It is completed by a short report of the discussion at the final plenary session, the closing peroration and the recommendations of the Roundtable.